Comunicação corporativa na comunicação pública: estudo de notícias de assessorias de imprensa de universidades públicas paulistas - Pirillo, Nádia Rubio [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The purpose of this experimental project was to characterize the reports by the press offices of three public universities in São Paulo higher education, two state and one federal, evaluating what prerogatives of corporate communication are present in the public communication made by them. From the perspective of the content analysis proposed by Laurence Bardin and; based on the concepts involved in the definition of public communication by Pierre Zémor and Corporate Communications by Jorge Duarte, it was made an analysis of the method of construction of news from the three universities. It was used a methodology in which interspersed of quantitative analysis procedures with qualitative analysis procedures
Keywords: Comunicação na administração publica; Comunicação nas organizações; Comunicação na educação; Imprensa; Assessoria; Communication in public administration; Communication in organizations; Communication in education; Press